Korupsi dan mentalitas: kendala kultural dalam pemberantasan korupsi di Indonesia - Listiyono Santoso; Dewi Meyriswati; Ilham Nur Alfian (Faculty of Social and Political Science, Universitas Airlangga, 2014)
Corruption is a complex act of crime. Its complexity does not only deal with legal issue but also social, political, and cultural issues. Law approach is more widely used in the eradication of corruption because corruption is a matter of law. However, seeing a corruption as a matter of law issue is the way to simplify the problem. The complexity of corruption makes this issue is feasibly approached through a variety of perspectives, one of those is cultural approach. The aim of this research is to reveal the cultural obstacles in eradicating corruption in Indonesia as well as to describe cultural conditions which led to a massive corruption. Formal juridical approach in eradicating corruption is considered to be done in a large number although they did not show maximal results. Such massive corruption in Indonesia seems to draw a conclusion that corruption has become a culture of the citizens of our nation. It means that there is a variety of cultural symptoms which encourage the act of corruption performed easily in every institution. There is a low mentality culture in the heart of the corruptor to carry out the action. That is why; we need a strategy in order to eradicate the culture of corruption in Indonesia.